The Efficiency of Baker's Yeast Autolysis Induced by Enzyme Preparations - M. V. Antonycheva; I. A. Kuzmichenko; A. K. Nikiforov; O. A. Volokh; I. V. Shulgina; S. A. Nizhegorodtsev (Проблемы особо опасных инфекций, 2009)
Has been analyzed the effect of enzyme preparations (trypsin, pepsin, pronase, proteovibrin - enzyme complex isolated from cultural ultrafiltrate of the industrial strain Vibrio cholerae M 41 Ogawa and from non-inactivated autolysate of yeasts) upon the process of autolysis of baker's yeast (Saccharomyses cerevisiae). The selected enzyme preparations being used in small doses render stimulatory effect to autolytic process thus reducing its duration and enabling to obtain autolysate with higher content of amine nitrogen.